Vampiric Remediation: The Vampire as a Self-Reflexive Technique in ‘Dracula’ (1897), ‘Nosferatu’ (1922) and ‘Shadow of the Vampire’ (2000) - Lehner, Alexander (Nordlit, 2019)
This paper aims at describing the self-reflexive functions of the vampire through the lens of remediation. First, I will describe remediation as the central form of representation used in the novel Dracula (1897). Its epistolary form remediates various contemporary high-tech media that are compiled as typewritten pages: It uses a hypermedia strategy. Dracula, the creature, mirrors this technique, since he and his abilities are an amalgamation of the characteristics of contemporary media. Dracula tries to remediate itself (that is to rehabilitate) in the shifting media-landscape of the outgoing 19th century and self-reflexively addresses this through the vampire’s connection to media. Second, Nosferatu: Eine Symphonie des Grauens (dir. Friedrich Wilhelm Murnau, 1922) deviates from this hypermedia strategy and argues for film’s immediacy. However, it also self-consciously addresses its state as an adaptation of Dracula and clearly acknowledges its medium when vampirism is involved within the film itself. Nosferatu connects vampirism with cinema and its techniques and, consequently, presents its vampire, ‘Count Orlok’, as a personification of film instead of an amalgamation of different media. Shadow of the Vampire (dir. Edmund Elias Merhige, 2000), then, is a refashioning within the medium: it is Nosferatu’s fictional making-of. Here, the borders between cinema and vampirism and between medium and reality collapse, as Shadow of the Vampire not only borrows the style and story of Nosferatu, but also incorporates the history and the myths surrounding the production of this seminal vampire movie. Consequently, it argues for film’s failure as a medium of immediacy facing the new hypermedia-landscape of the beginning 21st century. These three iterations of the vampire and remediation demonstrate how the vampire has been functionalized as a self-reflexive technique to speak about the medium it is depicted in, be it on the brink of a changing media-landscape, at the beginning of movies as the medium of immediacy, or its existence as an established art form at the emerging digital age.